The Education of d/Deaf and Hard of Hearing Children: Perspectives on Language and Literacy Development - Paul, Peter V. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
A significant number of d/Deaf and hard of hearing (d/Dhh) children and adolescents experience challenges in acquiring a functional level of English language and literacy skills in the United States (and elsewhere). To provide an understanding of this issue, this book explores the theoretical underpinnings and synthesizes major research findings. It also covers critical controversial areas such as the use of assistive hearing devices, language, and literacy assessments, and inclusion. Although the targeted population is children and adolescents who are d/Dhh, contributors found it necessary to apply our understanding of the development of English in other populations of struggling readers and writers such as children with language or literacy disabilities and those for whom English is not the home language. Collectively, this information should assist scholars in conducting further research and enable educators to develop general instructional guidelines and strategies to improve the language and literacy levels of d/Dhh students. It is clear that there is not a 'one-size-fits-all' concept, but, rather, research and instruction should be differentiated to meet the needs of d/Dhh students. It is our hope that this book stimulates further theorizing and research and, most importantly, offers evidence- and reason-based practices for improving language and literacy abilities of d/Dhh students.